2005
DOI: 10.1074/jbc.m500809200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biophysical Characterization of Photosystem I from Phytoene Desaturase and ζ-Carotene Desaturase Deletion Mutants of Synechocystis Sp. PCC 6803

Abstract: In photosystem I, oxidation of reduced acceptor A 1 ؊ through iron-sulfur cluster F X is biphasic with halftimes of ϳ5-30 ns ("fast" phase) and ϳ150 -300 ns ("slow" phase). Whether these biphasic kinetics reflect unidirectional electron transfer, involving only the PsaA-side phylloquinone or bi-directional electron transfer, involving both the PsaA-and PsaB-side phylloquinones, has been the source of some controversy. Brettel ؊ difference spectra, measured in cells and photosystem I complexes, retain the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
63
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 47 publications
15
63
0
Order By: Relevance
“…2A). This strain required glucose and dim light for growth and contained functional Photosystem I (PS I) but no PS II, as indicated by the absence of a variable chlorophyll fluorescence yield upon illumination of dark-adapted cells (27). Failure to isolate PS II core complexes using chromatographic methods also confirmed the absence of PS II centers in this strain.…”
Section: Modification Of Carotenoid Biosynthesis Pathway In Synechocymentioning
confidence: 83%
See 1 more Smart Citation
“…2A). This strain required glucose and dim light for growth and contained functional Photosystem I (PS I) but no PS II, as indicated by the absence of a variable chlorophyll fluorescence yield upon illumination of dark-adapted cells (27). Failure to isolate PS II core complexes using chromatographic methods also confirmed the absence of PS II centers in this strain.…”
Section: Modification Of Carotenoid Biosynthesis Pathway In Synechocymentioning
confidence: 83%
“…We have learned what types of carotenoids can be incorporated into PS II. We have found that gene deletions that block ␤-carotene formation do not result in PS II formation (27). However, expressing phytoene desaturase from Rhodobacter capsulatus in Synechocystis in place of the endogenous -carotene and phytoene desaturases, results in the accumulation of carotenoids that can be incorporated into PS II.…”
mentioning
confidence: 96%
“…Cell pellets were frozen in liquid nitrogen and freeze-dried. Pigments were extracted from freeze-dried cells by three successive extractions with methanol that contained 0.1% NH 4 OH, and extracts were combined and evaporated under a stream of nitrogen until the samples were dry. Dried samples were redissolved in a small volume of NH 4 OH-containing methanol and immediately subjected to high-performance liquid chromatography (HPLC) on an HP-1100 Chemstation with a Waters Spherisorb S5ODS2 (4.0 mm by 250 mm) column filled with C-18 reversed phase silica gel, using a linear 18-min gradient of ethyl acetate (0 to 95%) in acetonitrile-water-triethylamine (9:1:0.01, vol/vol/ vol) at a flow rate of 1 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…6G). To discriminate between effects due to the absence of just fucose (important for cell wall structure [38,57]) and of myxoxanthophyll, ⌬slr0940K, a strain lacking -carotene desaturase (CrtQ) that is needed for carotenoid formation (5,8), was included in this study as well: differences between the wild type and ⌬sll1213Z that are due to myxoxanthophyll should be visible also in ⌬slr0940K, which lacks myxoxanthophyll, whereas features shared by the wild type and ⌬slr0940K but not by ⌬sll1213Z presumably involve just fucose. As shown in Fig.…”
Section: Gdp-fucose Synthetase Gene Orthologuesmentioning
confidence: 99%